Free convection over a vertical plate in a micropolar fluid subjected to a step change in surface temperature - Mohd Rohni, Azizah; Omar, Zurni; Ibrahim, Adyda (Canadian Center of Science and Education, 2009)
The Keller box method has been employed for free convection over a vertical plate subjected to a step change in surface temperature in micropolar fluid. Numerical results presented include the reduced angular velocity profiles, development of wall shear stress or skin friction and development of the rate of change of the gyration component at the wall for various values of Prandtl numbers and temperature ratios. The study shows that the present results obtained in micropolar fluids, when temperature ratio 0w2=1, agree very well with the previous study without temperature change.